Territorial dimension in the internationalization of tourism destinations: Structuring factors in the post-COVID19 - Maria do Rosário Campos Mira; Lisete Mendes Mónico; Zélia Jesus Breda (Tourism & Management Studies)
This study presents an empirical validation of the territorial factors which contribute to the internationalization of tourism destinations. It is part of a broader investigation in which the dimensions and factors of tourism destinations’ internationalization were identified and four dimensions were validated: ‘territory’, ‘product’, ‘governance’ and ‘DMOs’. Here we present the path taken in terms of explaining the 'territorial' dimension. A cross-sectional study was carried out on Portuguese DMOs (n=470) with responsibilities in the areas of tourism and local or regional development. A questionnaire was elaborated and submitted to content, reliability and construct validations through exploratory and confirmatory factor analysis. For this purpose, we considered both a first and second order factor structure. The results sustain that the territorial factors influencing the internationalization of destinations are ‘resources’ (Factor 1), ‘economic activity’ (Factor 2) and ‘border’ (Factor 3). The relationship between political options of destinations’ internationalization and territories’ geographical, cultural and economic characteristics were determined. It is this relationship that forms the foundation of tourism in times of crisis, such as we are currently experiencing.